Preliminary Assessment of the Food Safety Modernization Act Analyzing the Center for Disease Control and Prevention Multistate Foodborne Outbreak Notices - Chambers, Delano A. (Transactions on Engineering and Computing Sciences, 2024)
As the rules of the Food Safety Modernization Act (FSMA) of 2011 takes root, foodborne outbreaks, and by extension related recalls, illnesses, and death should decrease. The Center for Disease Control and Prevention Multistate Foodborne Outbreak Notices provides data from October 2006 to current; a glimpse of food safety practices pre FSMA to date. An estimated 198 outbreak notices were reported October 2006 to December 2023 with 145 affiliated recalls, 23064 illnesses, and 132 deaths. While all organisms in the outbreak notices contributed to illnesses, Salmonella spp., Escherichia coli spp., and Listeria spp. could be considered the deadly three. Of the 198 outbreak notices, Salmonella spp. accounted for an estimated 50.51% outbreaks notices, 55.17% associated recalls, 68.56% illnesses, and 26.52% death; Escherichia coli spp. accounted for 24.75% outbreak notices, 21.38% recall, 9.35% illnesses, and 12.87% death. Listeria spp. accounting for 15.66% outbreak notices, 17.24% recall, 2.31% illnesses, and 60.61% death. Outbreak notices with associated recalls trended upwards from October 2006 to December 2023; illnesses slightly trended upwards; deaths appeared to flatline with a negligible downward movement. Data suggests more time needed to fully assess the impact the Food Safety Modernization Act has on foodborne outbreaks and resulting consequences post implementation.